Sonication time effect towards stability of Al2O3/PAG and SiO2/PAG Nanolubricants / A.A.M. Redhwan..[et al.] - A.A.M., Redhwan; W.H., Azmi; M.Z., Sharif; N.N.M., Zawawi; R., Mamat (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Ultrasonication is the act of applying sound force to agitate particles in a sample with the frequency of more than 20 kHz. It is an external vibration induced during preparation of nanolubricant that helps the particles to overcome the van der Waals force bonding. Nanolubricant prepared is intended to be used in automotive air conditioning (AAC) system to improve its performance. In this work, stability of Al2O3/Polyalkylene glycol (PAG) and SiO2/PAG nanolubricants of 0.2 % volume concentrations with different sonication time were investigated. Five samples for each nanolubricant were prepared by two-step method process with variation of sonication time from zero to two hours’ time with half an hour interval. The stability tests were done by visual sedimentation and UV-vis spectrometer. The optimum sonication time found to be one and half hours and two hours for Al2O3/PAG and SiO2/PAG nanolubricants respectively. Both nanolubricants were found stable for more than two weeks’ period.